Periglacial microclimate in low-altitude scree slopes supports relict biodiversity - Růžička, V. (Vlastimil); Zacharda, M.; Němcová, L.; Šmilauer, P.; Nekola, J. C. (Journal of Natural History, 2012)
Air circulation through talus slopes creates unique microclimates, with some of the most interesting being low elevation mid-latitude scree in areas with frequent snow-free <0°C (eg. “black frost”) days that allow for development of year-round ice accumulations. Here, we document this phenomenon on Kamenec Hill in North Bohemia (Czech Republic) located at an altitude of 330 m a.s.l., where mean annual temperatures under 0°C are maintained in a narrow strip along the slope’s lower margin. This microhabitat, as well as intersticial spaces between scree blocks elsewhere on this slope, supports an important assemblage of boreal and/or arctic bryophytes, pteridophytes and arthropods that are disjunct from their normal ranges far to the north. This freezing scree slope represents a classic example of a paleorefugium that significantly contributes to protection and maintenance of regional landscape biodiversity.